Unveiling the critical role of tall-stack emissions in winter nitrate episodes over North China through machine learning and 3D model analysis - Yang, Ting; Tian, Yutong; Wang, Zifa (Frontiers in Environmental Science, 2025)
Particulate nitrate (pNO3-) pollution persists over the North China Plain despite emission controls. We unravel a key mechanism: tall industrial stacks (≥210 m) release ammonia which, under strong winter oxidizing conditions, forms ammonium nitrate aloft. Utilizing a novel 3D high-resolution nitrate assimilation dataset and machine learning (XGBoost-SHAP), we tracked a major pollution event. Nitrate formed above 200 m accumulated in the nocturnal residual layer. Morning boundary layer development mixed this pollution downward, elevating surface concentrations by up to 35.5 μg m-3 within hours. Crucially, the Taihang and Yanshan Mountains south-westerly winds channeled, transporting the plume ∼400 km. Downwind urban heating and enhanced oxidants during winter (including COVID-19-period anomalies) further amplified nitrate production within the boundary layer. This study establishes a complete 3D picture of elevated nitrate formation, transport, and mixing, highlighting the need for targeted controls on elevated industrial sources and cross-regional strategies.